Modelling of stand-alone hybrid microgrid with demand-side management - Seifi, Mohammad (2014)
The future of power system will be highly influenced by Microgrid with renewable energy resources. Stand-alone Microgrid is widely proposed for any kind of grid-off community and rural electrification. Due to lack of established standards in Microgrid industry, designing a Microgrid seams ambiguous. The first part of this study tries to fill this gap by acquiring and addressing the relevant standards. The design starts by feasible study based on location and potential renewable energy resources. Based on load data, the supply capacity and storage backup are calculated. It was shown that solar and wind energy are suitable Renewable Energy Sources (RES) for tropical area such as Malaysia. In this study, solar energy, wind energy and battery backup are sized and modeled based on relevant standards. Three controllers are modeled and simulated for Maximum Power Point Tracking (MPPT), DC/DC converter and DC/AC inverters for proposed plant. Mathematical model of each individual elements of proposed Microgrid are modeled in MATLAB/Simulink software. The simulation results of main components are validated by manufacturer’s datasheet. Due to uncertainty and intermittency in Renewable Energy (RE) Generation, a smart Demand Side Management (DSM) controller is proposed to smoothing demand control and increase system efficiency. The existing DSM functions are mostly suitable for utilities and grid-connected Microgrid. Proposed DSM is adjusted to meet vulnerable stand-alone system requirement. The simulation results show DSM controller will supply sensitive load longer and will increase system efficiency. Different scenarios for sun irradiance, wind speed and temperature are simulated to test DSM controller in different situation and the result shows DSM controller is successfully implemented. For future study, an intelligent load pattern recognition will improve the proposed DSM function for each load will be recognized by DSM wherever they plugged in the supply. Finally, an experimental work on this study also is recommended.